MEASURING THE JOB PRECARIOUSNESS EXPERIENCED BY GOJEK DRIVERS IN INDONESIA - Mohammad Farid Budiono (GoAcademica Research dan Publishing, 2023)
The introduction provides an overview of the rapid growth of digital technology and its impact on various aspects of human life. The rise of the information society and the development of the digital economy, particularly in Indonesia, has led to the emergence of start-ups like Gojek. Gojek, a digital business offering various services, has become a significant player in the Indonesian market, impacting millions of lives and employing many driver-partners. However, the welfare of Gojek drivers has come under scrutiny as studies have highlighted their vulnerabilities. The concept of